Performance Government in Maine: The Effort to Make State Government More Efficient, Responsive, and Accountable - Clary, Bruce; Wechsler, Barton (Maine Policy Review, 1999)
Maine, like the federal government and many other states, has embarked upon a major initiative to change how government conducts its business. At the federal level this initiative has been called the National Performance Review. Spearheaded by Vice President Al Gore, its goal is nothing short of reinventing government so it performs better, costs less, and gets results. Today, many states have undertaken initiatives similar to the National Performance Review and the general term used to describe these activities is “performance government.” In Maine, a 1991 Special Commission on Governmental Restructuring marks the first time this concept was seriously talked about. Although performance government may apply to a wide range of administrative changes, it most typically applies to three reform initiatives: strategic planning, performance budgeting and performance contracting. Maine has been reinventing its government systems to include each of these components. This two-part symposium on performance government begins with this article by Bruce Clary and Barton Wechsler of the Muskie School of Public Service. Clary and Wechsler provide an overview of efforts to reinvent government and the context for Maine’s current initiatives.
Keywords: Maine state government; state government reform; performance government